Investigating the Proximity of the Lower Alveolar Canal to the Apex of Premolar and Molar Teeth in the Mandible Using Cone Beam Computed Tomography (CBCT) in Tabriz, Iran - Shahi, Shahriar; Kolahdouz, Shirin; Ghanbaran, Sahar; Gerayeli, Mohammad; Movahed, Emad; Irani, Mohammad Ali; Ghadimi, Shaghayegh (Galen Medical Journal, 2025)
Background: Knowing the anatomical link between the IAN and surrounding structures is vital before endodontic operations to avoid injuring the IAN. Examining the relationship between the inferior alveolar canal (IAC) and the apices of mandibular premolars and molars using cone beam computed tomography (CBCT) is the primary objective of this work. Materials and Methods: Two hundred and twenty patients, ranging in age from sixteen to seventy-seven, who visited the University of Tabriz’s Faculty of Dentistry had their CBCT images examined in this retrospective cohort study. Mandibular fractures, pathologies, or bone syndromes were not considered, as were teeth with diseases impacting canal contact. Additionally, poorly defined IAN pictures were not included. The shortest distance between the root apex and the upper border of the interosseous capsule was determined by taking measurements using cross-sections that were 0.3 mm thick. Results: Analysis of 220 CBCT images revealed a gender distribution of 56.8% female and 43.2% male patients, with age groups of 49 years (32.3%). The greatest mean distance between the teeth and the IAC was observed in the first premolar in males (5.7 mm), while the shortest was in the third molar in females (2.91 mm). Distances from mandibular molars and premolars to the IAC showed significant differences: second and first molars had smaller distal than mesial distances (P<0.05), and second premolars had greater distances on the right side (P<0.001). Males exhibited greater distances than females for molars and premolars (P<0.05), but age had no significant impact (P>0.05). Conclusion: Mandibular premolars maintain the most significant distance, while the third molar is closest to the IAC. Gender differences are significant, while age does not impact these measurements.